Brain-computer interface technology for speech recognition: A review - AlSaleh, Mashael M.; Arvaneh, Mahnaz; Christensen, Heidi; Moore, Roger K. (2016 Asia-Pacific Signal and Information Processing Association Annual Summit and Conference (APSIPA), 2016)
This paper presents an overview of the studies that have been conducted with the purpose of understanding the use of brain signals as input to a speech recogniser. The studies have been categorised based on the type of the technology used with a summary of the methodologies used and achieved results. In addition, the paper gives an insight into some studies that examined the effect of the chosen stimuli on brain activities as an important factor in the recognition process. The remaining part of this paper lists the limitations of the available studies and the challenges for future work in this area.